Gendered Taxes : The Interaction of Tax Policy with Gender Equality - Coelho, Maria (IMF Working Papers; Working Paper, 2022)
This paper provides an overview of the relation between tax policy and gender equality, covering labor, capital and wealth, as well as consumption taxes. It considers implicit and explicit gender biases and corrective taxation. On labor taxes, we discuss the well-established findings on female labor supply and present new empirical work on the impact of household taxation. We also analyze the impact of progressivity on pay gaps and labor supply. On capital and wealth taxation, we discuss the implications of lower effective capital income taxation on the personal income tax burden gap across genders. We show that countries with relatively low female shares of capital income and wealth also tend to tax property and inheritances particularly lightly. On consumption taxes, we cover taxes on female hygiene products and excise taxes, which we assess in relation to externalities and differences in consumption patterns across genders.